Analysis Of Waste Production Management And Environmental Conditions On Coating Process Performancebefore And After The Implementation Of Environmental Management System (EMS) - Yetty Dwi Lestari; Binar Prisilia (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2012)
The phenomenon of proactive environmental management began in the 1990's where manufacturing industries were aware  the importance of corporate sustainability through sustainable environmental management. Various strategies  can be done in a proactive environmental management. This study emphasized the development of conditions environmental performance companies  in minimizing waste, especially in production process that contains a lot of waste. The company has trying to implement a standardized EMS, through its own sludge wastewater treatment as a raw material for making bricks, while for solid waste (zinc dross and zinc ash), had been sold to external parties from the beginning. There isn’t recycling process, Galva furnace repair and improvement work on the system setting WWT or the WWTP. EMS implementation is strengthened through the acceptance of ISO 14000 in 2007. The condition of  Company's environmental performance related to waste minimization in the galvanizing process before and after implementing EMS was measured using input indicators (material), the input of water and energy use, and output of products in the form of waste (solid or sludge). The result did not correspond quantitatively with the indicators used in ISO 14000. Based on the quantitative result , a company processing  waste , did not change significantly.